2009
DOI: 10.1007/978-3-642-00255-7_22
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Path Reduction for Software Model Checking

Abstract: Abstract. We present the new technique of dynamic path reduction (DPR), which allows one to prune redundant paths from the state space of a program under verification. DPR is a very general technique which we consider here in the context of the bounded model checking of sequential programs with nondeterministic conditionals. The DPR approach is based on the symbolic analysis of concrete executions. For each explored execution path π that does not reach an abort statement, we repeatedly apply a weakest-precondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The main contributions are (1) a new symbolic encoding of executions of a multithreaded program, (2) using both under-and over-approximations in the same trace-driven abstraction framework, where refinement involving the mutual guidance between concrete program execution and symbolic analysis. For future work, we plan to investigate performance enhancement techniques, such as minimal unsatisfiable core analysis [23] and dynamic path reduction [31], to allow TDV to scale to larger programs.…”
Section: Discussionmentioning
confidence: 99%
“…The main contributions are (1) a new symbolic encoding of executions of a multithreaded program, (2) using both under-and over-approximations in the same trace-driven abstraction framework, where refinement involving the mutual guidance between concrete program execution and symbolic analysis. For future work, we plan to investigate performance enhancement techniques, such as minimal unsatisfiable core analysis [23] and dynamic path reduction [31], to allow TDV to scale to larger programs.…”
Section: Discussionmentioning
confidence: 99%
“…However they have not investigated its use in static analysis. Yang et al [26] propose the use of SMT solvers to remove infeasible paths by Dynamic Path Reduction. However, the work only addresses programs without pointers employing standard weakest precondition and it is not aimed at false positive elimination.…”
Section: Related Workmentioning
confidence: 99%
“…The rest of the report summarizes the main contributions of our research. More details about our research can be found in our publications [13,37,38,39,45,46,47] and a forthcoming Ph.D. thesis [36].…”
Section: Approach and Outlinementioning
confidence: 99%